2004
DOI: 10.1159/000076523
|View full text |Cite
|
Sign up to set email alerts
|

The Diverse Molecular Basis and Hematological Features of Hb H and AEBart’s Diseases in Northeast Thailand

Abstract: We defined the molecular basis and correlated the hematological phenotypes with the globin genotypes in 52 patients with Hb H disease and 29 patients with AEBart’s disease of northeast Thailand. Among the former group, the most prevalent molecular defect was found to be the interaction of α-thalassemia 1 (SEA type) with the Hb Constant Spring (Hb CS; 35 of 52 patients), followed by the deletion of three α-globin genes with the SEA type α-thalassemia 1 and the 3.7- or 4.2-kb deletion of α-thalassemia 2 (14 of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 20 publications
5
48
0
Order By: Relevance
“…Previous studies have demonstrated that interaction of α⁰-thalassemia and α + -thalassemia (which results in the Hb H disease) with heterozygous Hb E (Hb H/Hb E heterozygote) and homozygous Hb E (Hb H/Hb E homozygote) usually leads to complex αβ-thalassemia syndromes known as EABart’s and EFBart’s diseases, respectively [4]. Both diseases are usually accompanied by severe thalassemia intermedia phenotypes with detectable Hb F (α 2 γ 2 ) and Hb Bart’s (γ 4 ) due to an increased expression of the γ-globin gene [4, 5]. As shown in table 1, in these 2 groups, microcytosis and hypochromicity were more pronounced than in groups 1–6, and only modest elevation of Hb F was observed (3.0 ± 2.2 to 6.5 ± 3.6%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that interaction of α⁰-thalassemia and α + -thalassemia (which results in the Hb H disease) with heterozygous Hb E (Hb H/Hb E heterozygote) and homozygous Hb E (Hb H/Hb E homozygote) usually leads to complex αβ-thalassemia syndromes known as EABart’s and EFBart’s diseases, respectively [4]. Both diseases are usually accompanied by severe thalassemia intermedia phenotypes with detectable Hb F (α 2 γ 2 ) and Hb Bart’s (γ 4 ) due to an increased expression of the γ-globin gene [4, 5]. As shown in table 1, in these 2 groups, microcytosis and hypochromicity were more pronounced than in groups 1–6, and only modest elevation of Hb F was observed (3.0 ± 2.2 to 6.5 ± 3.6%).…”
Section: Discussionmentioning
confidence: 99%
“…The disease also carries an increased risk of maternal complications with severe preeclampsia, ante- and postpartum hemorrhage and lethal complications [3]. In addition, interaction of α⁰-thalassemia with α + -thalassemia leads to Hb H disease, and interaction of Hb H disease with Hb E can lead to complex αβ-thalassemia intermedia syndromes [4, 5]. Therefore, identification of α⁰-thalassemia carriers is an important step in genetic counseling, prevention and control of thalassemia in at-risk families.…”
Section: Introductionmentioning
confidence: 99%
“…Previously described gap-PCR and allele specific PCR (ASPCR) were used to identify six forms of α-thal mutations common in Southeast Asia, including SEA (NG_000006.1: g.26264_45564del19301) and THAI (NG_000006.1: g.10664_44164del33501) deletions causing α 0 -thal, −3.7 (NG_000006.1:g.34164_37967del3804) and −4.2 kb (exact deletion breakpoints are not available) deletions causing α + -thal, Hb CS (HBA2:c.427T>C), and Hb Ps (HBA2: c.429A > T) (Sanchaisuriya et al 2002;Fucharoen et al 2003;Boonsa et al 2004;Sae-ung et al 2006). Based on our experience of using these methods in routine practice, the false negative rate was less than 0.1%.…”
Section: Dna Analysismentioning
confidence: 99%
“…In addition, co-inheritance of a-thalassaemia with b-thalassaemia can ameliorate the clinical severity of b-thalassaemia disease. [3][4][5][6] Identification of athalassaemia is essential for providing appropriate genetic thalassaemia counselling to patients.…”
Section: Introductionmentioning
confidence: 99%